Building Ecological Resilience in Highly Modified Landscapes. (7th November 2018) - Beller, Erin E; Spotswood, Erica N; Robinson, April H; Anderson, Mark G; Higgs, Eric S; Hobbs, Richard J; Suding, Katharine N; Zavaleta, Erika S; Grenier, J Letitia; Grossinger, Robin M
Abstract: Ecological resilience is a powerful heuristic for ecosystem management in the context of rapid environmental change. Significant efforts are underway to improve the resilience of biodiversity and ecological function to extreme events and directional change across all types of landscapes, from intact natural systems to highly modified landscapes such as cities and agricultural regions. However, identifying management strategies likely to promote ecological resilience remains a challenge. In this article, we present seven core dimensions to guide long-term and large-scale resilience planning in highly modified landscapes, with the objective of providing a structure and shared vocabulary for recognizing opportunities and actions likely to increase resilience across the whole landscape. We illustrate application of our approach to landscape-scale ecosystem management through case studies from two highly modified California landscapes, Silicon Valley and the Sacramento–San Joaquin Delta. We propose that resilience-based management is best implemented at large spatial scales and through collaborative, cross-sector partnerships.